Slower Processing Speed in Autism Spectrum Disorder: A Meta-analytic Investigation of Time-Based Tasks. - Zapparrata, Nicole M.; Brooks, Patricia J.; Ober, Teresa M. (Journal of Autism & Developmental Disorders, 2023)
Autism spectrum disorder (ASD) is a complex neurodevelopmental condition affecting information processing across domains. The current meta-analysis investigated whether slower processing speed is associated with the ASD neurocognitive profile and whether findings hold across different time-based tasks and stimuli (social vs. nonsocial; linguistic vs. nonlinguistic). Mean RTs of ASD and age-matched neurotypical comparison groups (N = 893 ASD, 1063 neurotypical; mean age ASD group = 17 years) were compared across simple RT, choice RT, and interference control tasks (44 studies, 106 effects) using robust variance estimation meta-analysis. Simple RT tasks required participants to respond to individual stimuli, whereas choice RT tasks required forced-choice responses to two or more stimuli. Interference control tasks required a decision in the context of a distractor or priming stimulus; in an effort to minimize inhibitory demands, we extracted RTs only from baseline and congruent conditions of such tasks. All tasks required nonverbal (motor) responses. The overall effect-size estimate indicated significantly longer mean RTs in ASD groups (g =.35, 95% CI =.16;.54) than comparison groups. Task type moderated effects, with larger estimates drawn from simple RT tasks than interference control tasks. However, across all three task types, ASD groups exhibited significantly longer mean RTs than comparison groups. Stimulus type and age did not moderate effects. Generalized slowing may be a domain-general characteristic of ASD with potential consequences for social, language, and motor development. Assessing processing speed may inform development of interventions to support autistic individuals and their diverse cognitive profiles.